Negative electrode material and preparation method thereof

By using the method of roasting MOF materials and organic acid phosphating reaction in lithium-ion battery negative electrode materials, mixed multivalent metal phosphide particles and carbon nanotube composite materials are prepared, which solves the problem of low conductivity and volume of existing negative electrode materials. The expansion problem is eliminated and battery performance with high specific capacity, conductivity and stability is achieved.

CN119349519APending Publication Date: 2025-01-24SUZHOU JUFENG ELECTRICAL INSULATION SYST +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411421413.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The electronic/ion conductivity of existing lithium-ion battery anode materials is low, and there is a serious volume expansion effect during charging and discharging, which limits its application.

Method used

By calcining the MOF material under a reducing atmosphere to form a precursor material, and performing a phosphating reaction with an organic acid as an additive in an inert environment, a mixture of multivalent metal phosphide particles and carbon nanotubes wrapped around them is prepared. Negative material.

Benefits of technology

It improves the theoretical specific capacity, conductivity and structural stability of the material, and significantly improves the cycle stability performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005080905980000061
    Figure BDA0005080905980000061
  • Figure BDA0005080905980000071
    Figure BDA0005080905980000071
  • Figure HDA0005080905990000011
    Figure HDA0005080905990000011
Patent Text Reader

Abstract

The invention relates to a negative electrode material and a preparation method thereof, and the preparation method comprises the following steps: (1) roasting an MOF material in a reducing atmosphere to obtain a precursor material; and (2) the precursor material and an additive are uniformly mixed, then the uniformly mixed material is subjected to a phosphating reaction in an inert environment, the negative electrode material is obtained, the additive is organic acid, and the negative electrode material comprises metal phosphide particles in a mixed valence state and carbon nanotubes wound around the metal phosphide particles. According to the method, the organic acid is added into a phosphating reaction system, the organic acid can react with phosphorus steam or PH3 generated in the phosphating process, so that the phosphating speed of the metal phosphide is effectively reduced, hydroxyl in the organic acid can induce a part of phosphide to further generate valence state conversion, and then it is guaranteed that the product is the metal phosphide with three mixed valence states; the mixed-valence metal phosphide has high theoretical specific capacity, high conductivity and high structural stability, and the performance of the mixed-valence metal phosphide is more excellent than that of a single-valence metal phosphide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a negative electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of electric vehicles, energy storage and portable electronic products, the requirements for the electrochemical performance of lithium-ion batteries are becoming higher and higher. Electrode materials are the key factors affecting the electrochemical performance of batteries. In recent years, the research on positive electrode materials in the industry has made great progress, while the lack of high-performance negative electrode materials has hindered the development of lithium-ion batteries. Therefore, it is of great significance to research and develop lithium-ion battery negative electrode materials with excellent performance.

[0003] Metal phosphide is a kind of negative electrode material for lithium-ion batteries that has attracted much attention. It has the characteristics of suitable working potential and high specific capacity. However, its low electronic / ionic conductivity and severe volume expansion effect during charging and discharging limit its effective application. Patent CN 114229832 A uses hexahydrated cobalt nitrate as a cobalt source and 2-methylimidazole as a carbon source and nitrogen source to react at room temperature to obtain ZIF-67 cubes, and then calcines at high temperature under argon protection to obtain Co@NC-CNT nanomaterial cube precursors. Finally, sodium hypophosphite is used as a phosphorus source and phosphating is performed under argon protection to obtain nitrogen-carbon doped cobalt phosphide (CoP@NC-CNT) nanocube materials containing carbon nanotubes, and use them as negative electrode materials for lithium-ion batteries. Compared with ZIF-67 cubes, the conductivity and stability of this negative electrode material have been improved, but there is still room for further improvement. Summary of the invention

[0004] The object of the present invention is to provide a negative electrode material having high theoretical specific capacity, high conductivity and good structural stability and a preparation method thereof.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a negative electrode material comprises the following steps:

[0007] (1) calcining a MOF material (metal organic framework material) under a reducing atmosphere to obtain a precursor material;

[0008] (2) mixing the precursor material and the additive, and then subjecting the mixed material to a phosphating reaction in an inert environment to obtain a negative electrode material, wherein the additive is an organic acid, and the negative electrode material includes mixed multivalent metal phosphide particles and carbon nanotubes wrapped around the metal phosphide particles.

[0009] The present application adds an organic acid, which can react with the phosphorus vapor or PH3 generated during the phosphating process, thereby effectively slowing down the speed of metal phosphide phosphating, and the hydroxyl group in the organic acid can induce further valence transformation of part of the phosphide, thereby ensuring that the metal phosphide in the product is in three mixed valence states, and the mixed multivalent metal phosphide has high theoretical specific capacity, high conductivity and high structural stability, and its performance is better than that of the metal phosphide in a single valence state. In addition, the present application also reduces the metal in the MOF material to a metal element by roasting the MOF material under a reducing atmosphere, on the one hand, providing a metal raw material for the phosphating reaction, and on the other hand, the metal element can catalyze the carbon source of the MOF material at high temperature to form carbon nanotubes, which can effectively improve the conductivity of the material, and inhibit the volume expansion of the metal phosphide during the charge and discharge process, greatly improving the cyclic stability of the material.

[0010] Preferably, the organic acid is a weak organic acid.

[0011] Further preferably, the organic acid is fed in the form of powder.

[0012] In some embodiments, the organic acid is selected from one or more of salicylic acid, oxalic acid, and citric acid.

[0013] Preferably, the mass ratio of the precursor material to the additive is 100:(0.2-2), for example, 100:0.2, 100:0.5, 100:0.8, 100:1, 100:1.2, 100:1.5, 100:1.8, 100:2.

[0014] Preferably, the metal phosphide is cobalt phosphide.

[0015] In some embodiments, the cobalt phosphide is mainly composed of CoP, Co2P and CoP2.

[0016] Preferably, the phosphating agent used in the phosphating reaction is red phosphorus and / or sodium hypophosphite.

[0017] Preferably, the mass ratio of the phosphating agent to the mixed material is (3-30):1.

[0018] In some embodiments, when red phosphorus is used as the phosphating agent, the mass ratio of the red phosphorus to the mixed material is (3-10):1.

[0019] In some embodiments, when sodium hypophosphite is used as the phosphating agent, the mass ratio of the sodium hypophosphite to the mixed material is (10-30):1.

[0020] Preferably, step (2) specifically includes mixing the precursor material and the additive, then placing the mixed material and the phosphating agent in a tube furnace respectively, with the phosphating agent located upstream of the gas flow in the tube furnace, and then performing phosphating treatment in an inert environment.

[0021] Preferably, the temperature of the phosphating reaction is 300 - 500 °C, such as 300 °C, 350 °C, 400 °C, 450 °C, 500 °C.

[0022] Preferably, the time of the phosphating reaction is 1 - 5 h, such as 1 h, 2 h, 3 h, 4 h or 5 h.

[0023] Preferably, the inert environment is a vacuum environment, an argon environment, a nitrogen environment or a nitrogen - argon mixed environment.

[0024] In some embodiments, the inert environment is a nitrogen - argon mixed environment, where the mass ratio of nitrogen to argon is (90 - 99):(10 - 1).

[0025] Preferably, the temperature of the calcination is 500 - 1000 °C, such as 500 °C, 600 °C, 700 °C, 800 °C, 900 °C, 1000 °C.

[0026] Preferably, the time of the calcination is 1 - 24 h, such as 1 h, 2 h, 5 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h, 24 h.

[0027] Preferably, the reducing atmosphere is a hydrogen atmosphere, a carbon monoxide atmosphere, a methane atmosphere or a mixed atmosphere formed by any one of hydrogen, carbon monoxide, methane and argon and / or nitrogen.

[0028] Preferably, the MOF material is ZIF - 67.

[0029] The present invention also provides a negative electrode material, which includes mixed multi - valent Co x P particles and carbon nanotubes in - situ formed on the surface of the Co x P particles and wound around them, where 0.5 < x < 2, and the Co x P includes CoP, Co2P and CoP2.

[0030] Preferably, the mass ratio of the Co x P particles to the carbon nanotubes is 100:(1 - 10).

[0031] Preferably, the negative electrode material is prepared by the above - mentioned preparation method.

[0032] The present invention also provides an application of the negative electrode material in a lithium ion battery, wherein the application includes preparing a negative electrode using the negative electrode material.

[0033] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0034] The preparation method of the invention is simple and easy to operate. By adding an organic acid into the phosphating reaction system, the organic acid can react with phosphorus vapor or PH3 generated in the phosphating process, thereby effectively slowing down the phosphating speed of the metal phosphide. The hydroxyl group in the organic acid can induce further valence transformation of part of the phosphide, thereby ensuring that the product is a metal phosphide with three mixed valence states. The mixed multi-valence metal phosphide has high theoretical specific capacity, high electrical conductivity and high structural stability, and its performance is better than that of a single-valence metal phosphide. The invention also forms carbon nanotubes wrapped around the metal phosphide in situ on the surface of the metal phosphide, thereby further improving the electrical conductivity and cycle stability of the material.

[0035] The negative electrode material of the present invention has high theoretical specific capacity, good conductivity and excellent stability, and can be applied in a new generation of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is the XRD diagram of the negative electrode material in Example 1 of the present invention;

[0037] Figure 2 is a SEM image of the negative electrode material in Example 1 of the present invention;

[0038] Figure 3 This is the XRD diagram of the negative electrode material in Comparative Example 1 of the present invention;

[0039] Figure 4 This is a SEM image of the negative electrode material in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0040] The preparation methods in the prior art are difficult to prepare metal phosphides with mixed valence, and the prepared products are difficult to have high theoretical specific capacity, high conductivity and high stability.

[0041] The present application uses MOF materials as the substrate, specifically ZIF-67 as the substrate, and calcines at high temperature in a reducing atmosphere to form a single substance of Co (cobalt). The single substance of Co can react with the phosphating agent or the high-temperature decomposition product of the phosphating agent (such as PH3) in the phosphating reaction to first form a Co2P product, and then further phosphate to usually form CoP. By adding an organic acid to the phosphating system, the organic acid can react with the phosphating agent or the high-temperature decomposition product of the phosphating agent, thereby slowing down the conversion of Co2P to CoP. At the same time, the hydroxyl group in the organic acid can induce part of CoP to be converted into CoP2 under the action of PH3, ensuring that the final product is three mixed valence states of Cox P, mixed valence Co x P is mainly composed of CoP, Co2P and CoP2. The high theoretical specific capacity of CoP2 material, the high conductivity of Co2P material and the high structural stability of CoP make CoP x The electrochemical performance of P is better than that of single-valent cobalt phosphide materials. In addition, Co can catalyze the MOF carbon source to form carbon nanotubes at high temperature, and then x The carbon nanotubes wrapped around the P surface were formed in situ, and the Co x The P / CNTs composite material has better performance. The preparation method is simple, easy to operate, mild reaction conditions and good application prospects.

[0042] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0043] Unless otherwise specified, the raw materials and instruments involved in the following examples are commercially available products.

[0044] Example 1

[0045] 5 g of MOF material (ZIF-67) was calcined at 800° C. for 12 h in a hydrogen-argon mixed atmosphere (95% Ar / 5% H2) to obtain a precursor material.

[0046] The precursor material obtained above was mixed with salicylic acid accounting for 1% of its mass, and NaH2PO2 and the mixed material in a mass ratio of 20:1 were weighed and placed in a tube furnace, and NaH2PO2 was placed upstream of the gas flow of the tube furnace, and then phosphating was performed at 350°C in an argon environment for 2h to obtain mixed valence Co x P / CNTs negative electrode material A1, in which the mass fraction of CNTs accounts for 4.5%.

[0047] The mixed valence Co prepared in this embodiment x P / CNTs material XRD pattern Figure 1 From the XRD spectrum, we can see that the prepared Co x Co in P / CNTs materials x P is in a mixed valence state, including CoP, Co2P and CoP2.

[0048] The mixed valence Co prepared in this embodiment x SEM images of P / CNTs materials are shown in Figure 2 From the SEM image, we can see that the negative electrode material A1 is composed of granular Cox P and extended around Co x P particles are composed of carbon nanotubes around them.

[0049] Example 2

[0050] 5 g of MOF material (ZIF-67) was calcined at 500° C. for 12 h in a hydrogen-argon mixed atmosphere (95% Ar / 5% H2) to obtain a precursor material.

[0051] The precursor material obtained above was mixed with salicylic acid accounting for 1% of its mass, and NaH2PO2 and the mixed material in a mass ratio of 10:1 were weighed and placed in a tube furnace, and NaH2PO2 was placed upstream of the gas flow of the tube furnace, and then phosphating was performed at 500°C in an argon environment for 3h to obtain mixed valence Co x P / CNTs negative electrode material A2.

[0052] Example 3

[0053] 5 g of MOF material (ZIF-67) was calcined at 500° C. for 24 h in a CO atmosphere to obtain a precursor material.

[0054] The precursor material obtained above was mixed with 1.5% citric acid by weight, and NaH2PO2 and the mixed material were weighed in a mass ratio of 30:1, placed in a tube furnace, and NaH2PO2 was placed upstream of the air flow of the tube furnace, and then phosphating was performed at 300°C in a vacuum environment for 5 hours to obtain mixed valence Co x P / CNTs negative electrode material A3.

[0055] Example 4

[0056] 5 g of MOF material (ZIF-67) was calcined at 900° C. for 1 h in a methane atmosphere to obtain a precursor material.

[0057] The precursor material obtained above was mixed with 0.2% oxalic acid by weight, and red phosphorus and the mixed material were weighed in a mass ratio of 10:1, placed in a tube furnace, and the red phosphorus was placed upstream of the air flow of the tube furnace, and then phosphating was performed at 350°C in a vacuum environment for 1 hour to obtain mixed valence Co x P / CNTs negative electrode material A4.

[0058] Example 5

[0059] 5 g of MOF material (ZIF-67) was calcined at 600° C. for 18 h in a hydrogen-argon mixed atmosphere (95% Ar / 5% H2) to obtain a precursor material.

[0060] The precursor material obtained above was mixed with oxalic acid accounting for 2% of its mass, and red phosphorus and the mixed material were weighed in a mass ratio of 3:1, placed in a tube furnace, and the red phosphorus was placed upstream of the air flow of the tube furnace, and then phosphating was performed at 350°C in a vacuum environment for 5 hours to obtain mixed valence Co x P / CNTs negative electrode material A5.

[0061] Comparative Example 1

[0062] Comparative Example 1 is the same as Example 1 except that no additive (salicylic acid) is added. The details are as follows:

[0063] 5 g of MOF material (ZIF-67) was calcined at 800° C. for 12 h in a hydrogen-argon mixed atmosphere (95% Ar / 5% H2) to obtain a precursor material.

[0064] NaH2PO2 and the above-obtained precursor material in a mass ratio of 20:1 were weighed and placed in a tubular furnace, and NaH2PO2 was placed upstream of the gas flow of the tubular furnace, and then phosphating was performed at 350°C in an argon environment for 2 hours to obtain the negative electrode material B1.

[0065] The XRD pattern of the material prepared in this comparative example is shown in Figure 3 From the XRD graph, we can see that the material is CoP / CNTs, indicating that the phosphide in the material B1 prepared without adding additives is in a single valence state. From the electrochemical performance comparison table 1, we can see that the rate and cycle performance of the single valence CoP / CNTs material are significantly inferior to those of the multivalent Co x P / CNTs.

[0066] Comparative Example 2

[0067] The difference from Example 2 is that a one-step calcination method is used, and the other conditions are the same. The details are as follows:

[0068] Take 5g of MOF material (ZIF-67) and mix it with 1% salicylic acid by mass, weigh NaH2PO2 and the mixed material in a mass ratio of 20:1, place it in a tube furnace, and place NaH2PO2 upstream of the gas flow of the tube furnace, treat it at 500℃ for 12h in a hydrogen-argon mixed atmosphere (95% Ar / 5% H2), and then switch to argon atmosphere for 3h (temperature unchanged), and obtain Co x P / C negative electrode material B2.

[0069] The Co prepared in this comparative example x SEM images of P / C negative electrode materials are shown in Figure 4 From the SEM image, we can see that the composite material is mainly granular Co x In the P / C material, no carbon nanotubes were found, indicating that the one-step calcination method could not form carbon nanotubes entangled in Co xThe electrochemical performance comparison table 1 shows that Co x When there are no carbon nanotubes entangled on the P surface, the electrochemical performance of the negative electrode material is poor.

[0070] Comparative Example 3

[0071] This comparative example is substantially the same as Example 1, except that the amount of salicylic acid used is different.

[0072] 5 g of MOF material (ZIF-67) was calcined at 800° C. for 12 h in a hydrogen-argon mixed atmosphere (95% Ar / 5% H2) to obtain a precursor material.

[0073] Salicylic acid and precursor materials were mixed at a mass ratio of 10:100, and NaH2PO2 and the mixed materials were weighed at a mass ratio of 20:1, placed in a tube furnace, and NaH2PO2 was placed upstream of the gas flow of the tube furnace, and then phosphating was performed at 350 ° C for 2 h in an argon environment to obtain mixed valence Co x P / CNTs negative electrode material B3. Analysis shows that the mass fraction of CNTs in negative electrode material B3 accounts for 11.2%. From the electrochemical performance comparison table 1, it can be seen that although the cycle performance of negative electrode material B3 is similar to that of A1, the discharge specific capacity and rate performance are greatly reduced, indicating that the excessive amount of salicylic acid used causes the CNTs content to be too high, which also leads to poor performance.

[0074] Comparative Example 4

[0075] This comparative example is substantially the same as Example 1, except that the amount of salicylic acid used is different.

[0076] 5 g of MOF material (ZIF-67) was calcined at 800° C. for 12 h in a hydrogen-argon mixed atmosphere (95% Ar / 5% H2) to obtain a precursor material.

[0077] Salicylic acid and precursor materials were mixed at a mass ratio of 0.1:100, and NaH2PO2 and the mixed materials were weighed at a mass ratio of 20:1, placed in a tube furnace, and NaH2PO2 was placed upstream of the air flow of the tube furnace, and then phosphating was performed at 350°C in an argon environment for 2h to obtain Co x P / CNTs negative electrode material B4. From the electrochemical performance comparison table 1, it can be seen that the rate performance and cycle performance of negative electrode material B4 have decreased significantly. This may be because the amount of salicylic acid used is too small, which makes Co x Phosphides in P / CNTs are mainly in the form of monovalent CoP, and other valence states of Co x The P content is too low.

[0078] Performance Test:

[0079] Under the same conditions, the negative electrode materials A1-A5 and B1-B4 were made into lithium-ion batteries, and the electrochemical properties of the batteries were tested. The test results are shown in Table 1.

[0080] Battery assembly: Weigh the above negative electrode materials, binder PVDF and conductive carbon black in a mass ratio of 8:1:1, mix and grind evenly, add appropriate amount of N-methylpyrrolidone, evenly coat on copper foil, dry at 80℃ for 2h, and roll at 20MPa. The prepared negative electrode sheet, sodium sheet, nickel foam, electrolyte (NaClO4, NC-034), diaphragm (glass fiber GF / D) and battery shell are assembled and sealed in a glove box filled with argon to prepare 2025 button batteries.

[0081] Electrochemical performance test method: The electrochemical charge and discharge test was carried out by first discharging at a constant current and then charging at a constant current, with a voltage range of 0.01-3 V. Discharge at a constant current to a termination voltage of 0.01 V; let stand for 5 min; charge at a constant current to a termination voltage of 3.0 V; let stand for 5 min; select 0.1C and 1C at a rate of 1C, cycle 1000 times, and measure its discharge specific capacity.

[0082] Table 1

[0083]

[0084]

[0085] It can be seen from the above table that the negative electrode material prepared in the present application has better rate performance and cycle performance when used in lithium-ion batteries.

[0086] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode material, characterized in that: The preparation method comprises the following steps: (1) calcining the MOF material under a reducing atmosphere to obtain a precursor material; (2) mixing the precursor material and the additive, and then subjecting the mixed material to a phosphating reaction in an inert environment to obtain a negative electrode material, wherein the additive is an organic acid, and the negative electrode material includes mixed multivalent metal phosphide particles and carbon nanotubes wrapped around the metal phosphide particles.

2. The method for preparing the negative electrode material according to claim 1, characterized in that: The additive is selected from one or more of salicylic acid, oxalic acid and citric acid; and / or, The feed mass ratio of the precursor material to the additive is 100:(0.2-2).

3. The method for preparing the negative electrode material according to claim 1, characterized in that: The metal phosphide is cobalt phosphide in mixed multivalent states.

4. The method for preparing the negative electrode material according to claim 1, characterized in that: The phosphating agent used in the phosphating reaction is red phosphorus and / or sodium hypophosphite.

5. The method for preparing the negative electrode material according to claim 4, characterized in that: The mass ratio of the red phosphorus to the mixed material is (3-10):1, and the mass ratio of the sodium hypophosphite to the mixed material is (10-30):

1.

6. The method for preparing the negative electrode material according to claim 1, characterized in that: The temperature of the phosphating reaction is 300-500° C.; and / or, The phosphating reaction time is 1 to 5 hours; and / or, The inert environment is a vacuum environment, an argon environment, a nitrogen environment, or a nitrogen-argon mixed environment.

7. The method for preparing the negative electrode material according to claim 1, characterized in that: The calcination temperature is 500-1000°C; and / or, The calcination time is 1 to 24 hours; and / or, The reducing atmosphere is a hydrogen atmosphere, a carbon monoxide atmosphere, a methane atmosphere, or a mixed atmosphere formed by any one of hydrogen, carbon monoxide, and methane and argon and / or nitrogen.

8. The method for preparing the negative electrode material according to claim 1, characterized in that: The MOF material is ZIF-67.

9. A negative electrode material, characterized in that: The negative electrode material includes Co with mixed multivalent states x P particles and carbon nanotubes that are in-situ formed on the surface of the Co x P particles and wound around them, where 0.5 < x < 2, and the Co x P includes CoP, Co2P, and CoP2.

10. The negative electrode material according to claim 9, characterized in that: The Co x The mass ratio of P particles to carbon nanotubes is 100:(1-10).

Citation Information

Patent Citations

  • Preparation method of nitrogen-carbon-doped cobalt phosphide nanocube material containing carbon nanotubes and lithium ion battery negative electrode material prepared from nitrogen-carbon-doped cobalt phosphide nanocube material

    CN114229832A